Penegakan Hukum Atas Praktik Penyimpangan Pembayaran Uang Saku Bagi Peserta Magang Di Daerah Istimewa Yogyakarta - Putri Shania Azizah Dinnar; Ayunita Nur Rohanawati (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Apprenticeships are increasingly in demand to prepare Indonesia’s workforce, yet many participants don’t receive their entitled allowances. This study addresses two issues: How are the legal provisions regarding allowances and wages for apprenticeship participants in Indonesia? And how is law enforcement implemented for participants not receiving allowances in the Special Region of Yogyakarta? Utilizing a juridical-empirical method with both statutory and socio-legal approaches, the study employed purposive sampling to gather data through interviews and questionnaires. The findings reveal that, first, wages are regulated by PP No. 36/2021 jo. PP No. 51/2023 and based on Labor Law is the right of workers based on employment agreements. Meanwhile, allowances are regulated by Permenaker No. 6/2020 and according to interviewee, are a form of appreciation given to interns based on internship agreements. Second, the regulations don’t stipulate sanctions; enforcement for student interns is based on mutual agreements, while for graduates, the Yogyakarta Manpower Inspectorate issues two inspection notices. The study recommends that the government define and standardize allowance amounts and revise regulations to include strict sanctions while strengthening the oversight role of the local labor office.